2011
DOI: 10.1100/tsw.2011.140
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of DNA Damage in Common Carp (Cyprinus carpioL.) by Comet Assay for Determination of Possible Pollution in Lake Mogan (Ankara)

Abstract: Contamination of the aquatic environment with various concentrations of pollutants results in unexpected threats to humans and wildlife. The consequences of exposure and metabolism of pollutants/xenobiotics, especially carcinogens and mutagens, can be suitably assessed by investigating severe events, such as DNA damage; for example, DNA adducts and DNA strand breaks. One of the commonly used techniques to detect DNA damage in aquatic organisms is single-cell gel electrophoresis (comet assay). This study was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 38 publications
1
6
0
1
Order By: Relevance
“…were both significantly higher ( P = 0) than in fish from the reference site (0.31 and 12.80, resp.). Tail moment in carp ( Cyprinus carpio ) from the Lake Mogan, which is under pollution stress of agricultural activities, was 1.50 ± 1.48 [ 24 ], which is a similar result to the one obtained in the present study (1.28 ± 1.41).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…were both significantly higher ( P = 0) than in fish from the reference site (0.31 and 12.80, resp.). Tail moment in carp ( Cyprinus carpio ) from the Lake Mogan, which is under pollution stress of agricultural activities, was 1.50 ± 1.48 [ 24 ], which is a similar result to the one obtained in the present study (1.28 ± 1.41).…”
Section: Resultssupporting
confidence: 89%
“…However, the main disadvantage of this parameter is that two cells with different tail lengths may have the same degree of tail intensity and may produce the same result. A major advantage when using the tail moment as an index of the DNA damage is that both the amount of the damaged DNA and the distance of the genetic material migration in the tail are represented by a single number [ 24 ]. Which parameter of DNA migration will be applied often depends on the personal preferences of the investigator.…”
Section: Resultsmentioning
confidence: 99%
“…Marcon et al (2010) found that a high content of certain metals in the water could be one of the factors that might cause genetic damages in fish. The comet assay has been successfully used to investigate effects of genotoxic pollutants on the integrity of DNA (Çok et al, 2011;Ferraro et al, 2004;Scalon et al, 2010). Micronucleus test was the only genotoxicity test applied thus far on barbel specimens from the natural population in the Danube River (Boettcher et al, 2010).…”
Section: Genotoxicity Due To Heavy Metalsmentioning
confidence: 99%
“…Three measures of DNA migration are commonly used: tail length, OTM, and % of the DNA in tail (tail intensity) [30][31][32]. Although OTM appeared to be the most statistically significant measurement [33], the inter-laboratory comparison of results seems to be difficult for this parameter [34].…”
Section: Discussionmentioning
confidence: 99%